Hubungan Pengetahuan Keluarga dengan Penanganan Awal Kejadian Strokedi Rsud Prof. Dr. Aloei Saboe - Sri Elisa Nento; Harismayanti Harismayanti; Fadli Syamsuddin (Jurnal Ventilator, 2023)
Stroke is a major health problem in the world. Stroke is the third cause of death in the world after coronary heart disease and cancer. Stroke, both ischemic and hemorrhagic, can have an impact on the sufferer. The aim is to determine the relationship between family knowledge and behavior and early management of stroke events. The research design is a correlative descriptive study with a cross sectional approach. This research was carried out in the Internal Room of HCU lt1 and G3 Neuro lt1 Prof. Hospital. Dr. Aloei Saboe. The number of samples is 67 people. The results showed that the average family knowledge of stroke patients was sufficient with a total of 45 respondents (67.2%), the initial treatment of families in most stroke patients was insufficient with a number of 41 respondents (61.2%). The results of the chi-square analysis test obtained a p-value = 0.000 <? 0.05, so it can be concluded that there is a relationship between family knowledge and the initial treatment of stroke patients. The existence of this research is expected to add to and increase family knowledge in the initial management of stroke patients.